Characterization of Coccidioides immitis isolates by restriction fragment length polymorphisms. - Zimmermann, C R (1994)
The marked increase in the number of cases of coccidioidomycosis in California in 1992 led to a study of isolates from various patients and environmental sources by restriction fragment length polymorphism (RFLP) analysis. Of 15 different isolates, most of the isolates (13 of 15) from California and 1 from Venezuela yielded one main RFLP pattern with evidence of two subgroups. The other two isolates (both from patients in the San Joaquin Valley of California) yielded a different RFLP pattern.